Interdisciplinary Class Observation in Higher Education: Lessons Learned from the Professional Development Experience of Four Teachers - Joana P. Miranda; Mariana Batista; Cristina Duarte; Tatiana Sanches (MDPI AG, 2021)
Peer observation of teaching has been adopted as a method to improve the quality of teaching. It involves observers providing descriptive feedback to their peers on learning and teaching practices. However, although extensively described in the literature in the education field, its use as a tool for development beyond teaching skills has not been explored deeply, nor the best practices described. Therefore, the objective of this study was to compare quantitative with qualitative peer observation, as well as to investigate the role of interdisciplinarity in the observation process. The present study results from experimental observation work carried out by four professors of higher education. Veterinary science, social work, pharmaceutical sciences, and education, the disciplinary areas of origin of the teachers, were the ecosystems in which the initial observation techniques were explored and applied, and the intention was to share good practices and pedagogical improvements through peer support. This study reports the experience of building an observation grid and its application, as well as the lessons learned during the observation experience. The aim was to evaluate whether the constructive criticism was focused on the pedagogical practices rather than on the content, which can be useful in understanding if the learning objectives are being attained, from the teacher's point of view. As such, we employed and assessed peer observation as a constructive, developmental process for higher education teachers from different fields of knowledge. The study concludes that feedback by peers is essential for the development of professional practice in higher education teaching, with the experience of qualitative observation being a fundamental path for teacher self-reflection in the search for their own authenticity. It further supports the notion that interdisciplinary differences, methodologies, styles, contexts, and practices can be used in a constructive way to improve course content and delivery, and, ultimately, to reinforce good teaching.